THE EFFECTIVENESS OF THE IMPLEMENTATION OF THE RESPONSIBILITY OF THE FATHER AGAINST THE LIVELIHOOD OF THE CHILD AFTER DIVORCE IN THE MAKASSAR IA CLASS RELIGION COURT - Sitti Hilmiah; Ma’ruf Hafidz; Ilham Abbas (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal